FORMATION OF SOCIAL CREATIVITY IN FUTURE EDUCATIONAL MANAGERS AND MODERNIZATION OF ITS ORGANIZATIONAL AND MANAGEMENT MECHANISMS (Scientific journal of the Fergana State University, 2025)
In this article, the theoretical and methodological foundations of improving the organizational and management mechanisms for the formation of social creativity in future educational managers and the tasks of forming social creativity in future educational managers are studied based on advanced foreign experiences. Also, theoretical aspects of the formation of social creativity in future educational managers were analyzed.